A Type of Reduplication in Turkish - Taneri, Mubeccel (Kansas Working Papers in Linguistics, 1990)
This is an attempt to describe one of several types of reduplication in Turkish, based on a piece of data elicited from 32 native speakers.* What was known as irregular case revealed itself as a complicated pattern of dissimilation. Although some rules postulated can account for most of the data, some varying forms call for more research for a more unified explanation.